Inactivation of Acinetobacter baumannii Biofilms on Polystyrene, Stainless Steel, and Urinary Catheters by Octenidine Dihydrochloride - Narayanan, Amoolya; Nair, Meera S.; Karumathil, Deepti P.; Baskaran, Sangeetha A.; Venkitanarayanan, Kumar; Amalaradjou, Mary Anne Roshni (Frontiers in Microbiology, 2016)
Acinetobacter baumannii is a major nosocomial pathogen causing human infections with significant mortality rates. In most cases, infections are acquired through exposure to A. baumannii biofilms that persist on contaminated hospital equipment and surfaces. Thus, it is imperative to develop effective measures for controlling A. baumannii biofilms in nosocomial settings. This study investigated the efficacy of octenidine dihydrochloride (OH), a new generation disinfectant for reducing A. baumannii biofilms on polystyrene, stainless steel and catheters. OH at 0.3% (5 mM), 0.6% (10 mM) and 0.9% (15 mM) was effective in significantly inactivating A. baumannii biofilms on all tested surfaces (P<0.05). Furthermore, OH was equally effective in inactivating biofilms of multidrug resistant and drug susceptible A. baumannii isolates. In addition, confocal imaging revealed the predominance of dead cells in the OH-treated samples in comparison to the control. Further, scanning electron microscopy of biofilms formed on catheters revealed that OH treatment significantly reduced A. baumannii biofilm populations in corroboration with our antibiofilm assay. These data underscore the efficacy of OH in inactivating A. baumannii biofilms, thereby suggesting its potential use as a disinfectant or a catheter lock solution to control A. baumannii infections.